Efecto antibacteriano del extracto etanólico de Ocimum basilicum (albahaca) sobre Staphylococcus aureus y Escherichia coli, Chiclayo-2021 - Malca Rivas, Antonio Herman; Osores Falla, Janeth Vanessa (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
El estudio tuvo por objetivo determinar el efecto antibacteriano del extracto etanólico de Ocimun basilicum sobre Staphylococcus aureus y Escherichia coli. Para el estudio se prepararon concentraciones del 100% y 50%, el efecto antibacteriano se determinon mediante la técnica de difusión en pozo. Los resultados mostraron que EL extracto etanólico de Ocimun basilicum al 100% frente a Staphylococcus aureus obtuvo halo de inhibición promedio de 14,87 mm y con el 50% fue de 11,43 mm, por otro lado, el mismo extracto expuesto a Escherichia coli a la concentración del 100% obtuvo halo de inhibición de 23,67 mm y con el 50% obtuvo halo de 18,87 mm. Se concluye que el extracto etanólico de Ocimun basilicum (albahaca) presenta efecto antibacteriano frente a Staphylococcus aureus y Escherichia coli

The objective of the study was to determine the antibacterial effect of the ethanolic extract of Ocimun basilicum on Staphylococcus aureus and Escherichia coli. For the study, concentrations of 100% and 50% were prepared and the antibacterial effect was determined by the well diffusion technique. The results showed that the ethanolic extract of Ocimun basilicum at 100% against Staphylococcus aureus obtained an average inhibition halo of 14.87 mm and with 50% it was 11.43 mm, on the other hand, the same extract exposed to Escherichia coli at 100% concentration obtained an inhibition halo of 23.67 mm and with 50% it obtained a halo of 18.87 mm. It is concluded that the ethanolic extract of Ocimun basilicum (basil) presents antibacterial effect against Staphylococcus aureus and Escherichia coli
Antibacterial effect of the ethanolic extract of Ocimum basilicum (basil) on Staphylococcus aureus and Escherichia coli, Chiclayo-2021
Keywords: Staphylococcus aureus; Escherichia coli; Ocimun basilicum; Extracto etanólico; Albahaca; https://purl.org/pe-repo/ocde/ford#3.01.05